Roger Taylor and Elenni Taylor and John Hotschilt and Kathleen Hotschilt interviewed by Alex Hood and Annette Hood in the Alex Hood folklore collection - Taylor, Roger, 1939-; Taylor, Elenni, 1956-; Hotschilt, John, 1972-; Hotschilt, Kathleen, 1972-; Hood, Alex, 1935-; Hood, Annette, 1948- (2008)
Roger Taylor speaks about his birth and background; his education; his interest in music; arrival in Australia; learning guitar; attending University; his interest in folk music and clubs; lecturing at Townsville University; starting Folk Club at the Univeristy; Palm Creek Festival becoming a family festival. Roger, Lenni, John and Kathleen talk about the organisation of the Festival and Folk Club; the cyclone event in 2000.
John and Kathleen speak about how they met; referring to their band and others; Peter Dymond-Ramplin; backpackers volunteering for Palm Creek Festival; Country Music Club; Youth Clubs controlling musical styles; the Rock and Roll and Folk boom. John talks about the history of Folk and Music Club; discussion about styles of music and performance; Australian pop; the importance of tradition; the pioneers of music in Townsville; well know artists performing in Townsville Folk Club; Martin Pearson; development of media involvement; needing to transfer to a new permanent site for Festival; needing a business plan; difficulties in obtaining consensus.
Recorded on 3 September 2008, in Townsville, Qld.
Digital master available
Timed summary available.
Keywords: Taylor, Roger, -- 1939- -- Interviews; Taylor, Elenni, -- 1956- -- Interviews; Hotschilt, John, -- 1972- -- Interviews; Hotschilt, Kathleen, -- 1972- -- Interviews; Folk musicians -- Australia -- Interviews; Folk musicians